UJI PEMANFAATAN AIR BUANGAN HATCHERY BUDIDAYA IKAN LAUT UNTUK PENDEDERAN IKAN KERAPU HIBRID CANTANG - Supii, Apri Imam; Inas Aprillia, Thania; Adi Sulianto, Akhmad; Lusiana, Novia (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2020)
Buleleng Regency has the potential to develop a hybrid cantang grouper aquaculture business. However, the cultivation business in Buleleng Regency on average does not have its own waste disposal site. Ammonia is the most dangerous content of aquaculture waste for marine life. Ammonia can cause an increase and accumulation of levels of inorganic compounds that can trigger toxins for some organisms to increase the prevalence of pathogens and certain fish diseases in the waters. One treatment that can be done in reusing wastewater is to make wastewater as a place to live fish by processing using filtration and disinfection methods, namely using silica sand media, zeolite, activated charcoal, palm fiber and ultraviolet (UV). The purpose of this study is to test the feasibility of water before and after filtration, and determine the best type of water for the Cantang hybrid grouper nursery. The method used in this research is a quantitative method using RAL (Completely Randomized Design) with three treatments and four replications. After that an analysis using ANOVA is used to determine the effect of the treatment given on the parameters tested. In the study, the water quality after filtration and disinfection treatment was better than the water quality before filtration and disinfection treatment, it can be seen in the ability of the filtration and disinfection method in reducing ammonia, nitrite and total bacterial colonies by 41.30%, 79.75%, and 76.92%, and increase the water pH and phosphate levels to 7.50 and 27.36%. In addition, the use of filtration and disinfection water can increase the survival of fish by 7.14% compared to using sea water. The survival of groupers using filtration and disinfection water is 100% while sea water is only 92.86% and wastewater is 57.14%. Filtration water can reduce bacteria compared to sea water and waste water. Except for the salinity, ammonia and phosphate parameters which still do not meet the standards. Key Word : Grouper Fish, UV Light, Water Filtration